Analisis Kepuasan Pelanggan PT. Era Energi Krazu Nusantara dengan Metode Service Quality dan Importance Performance Analysis - Andre Viola; Moh Jufriyanto; Efta Dhartikasari Priyana (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2023)
Quality of service as one of the efforts of PT. Era Krazu Energi Nusantara to continuously improve the quality of all processes, services and products produced. Based on the results of interviews with customers, complaints related to service quality and customer satisfaction are influenced by several factors, apart from product quality and price, the most important of which are service quality and personal factors that annoy individual customers. The results of the study using the Service Quality and Importance Performance Analysis methods, on the quality of service, it is known that there are several attributes indicating that the current quality of service is still not as expected by customers. Based on the calculation of Gap 5 from the service quality questionnaire, the highest results were obtained and had an effect on service quality, namely attribute X4 with a gap value of -0.33823, which is a strategic location attribute. Based on Importance Performance Analysis, the highest value is obtained from the attribute value in quadrant I at X7 (Employees' willingness to handle complaints quickly), and X11 (Employees are honest with consumers).